Impact of Fennel Essential Oil as an Antibiotic Alternative in Rabbit Diet on Antioxidant Enzymes Levels, Growth Performance, and Meat Quality - Tharwat Imbabi; Islam Sabeq; Ali Osman; Kamal Mahmoud; Shimaa A. Amer; Aziza M. Hassan; Nikolay Kostomakhin; Walid Habashy; Ahmed A. Easa (MDPI AG, 2021)
In the current study, fennel essential oil was used as an antibiotic alternative compared to gentamycin for enhancing the expression of apoptosis genes and antioxidant enzymes in weaned rabbits as well as meat quality and growth performance. The gene expression of the cell lymphoma 2 (BAX and BCL2), caspase3 (CASP3), and glutathione peroxidase (GPX1) were estimated in the liver tissue using qRT-PCR. A total of 45 Moshtohor weaned male rabbits aged four weeks were randomly allocated to control, T1, and T2 treatment groups; each consisted of 15 weaned male rabbits with five replicates. Rabbits in the T1 and T2 groups were orally supplied with 1 mL fennel oil and 1 mL gentamycin, respectively. Weaned rabbits under different treatments showed increased body weight (BW) at 8 and 12 weeks of age and average daily gain (ADG) at 4-8 and 4-12 weeks of age compared to the control group. Compared to the controls, the weaned rabbits supplemented with fennel oil and gentamycin had lower total cholesterol, triglyceride, and MDA. In addition, villus length, mRNA of BAX, BCL2, Casp3, and GPX were increased in the different treatments compared to the control. Furthermore, the meat of these rabbits was less tender, had a lower aerobic plate count (APC), pH, and was brighter and redder in color than the control. Under the conditions of the present study, the supplementation of weaned Moshtohor rabbits with fennel oil as a natural alternative for gentamycin enhanced feed conversion and daily gain through enhancing villus length and mucus thickness. Additionally, fennel essential oil reduces oxidative stress by increasing the antioxidant enzymes.